EFEKTIVITAS MEDIA PEMBALAJARN INTERAKTIF BERBASIS APLIKASI CANVA DALAM MATA KULIAH DESAIN MEDIA INTERAKTIF - Rini Novita; Satrio Junaidi; Syaiful Zuhri Harahap (Jurnal Edik Informatika Penelitian Bidang Komputer Sains dan Pendidikan Informatika, 2023)
An Interactive This environment is designed to allow users to control the flow of learning materials, interact with learning materials, and receive immediate feedback on success or failure in understanding the material. The purpose of this research is to implement Canva application in interactive media design course. This research uses descriptive quantitative research methods. Data collection techniques are carried out by looking at conditions, situations, phenomena or various research variables. The results of this study indicate that the use of the Canva Application in the interactive media design course of the Informatics Engineering Education Study Program at University PGRI Sumatera Barat can increase student effectiveness in designing interactive media. The Canva application allows students to create interactive media designs easily without having to have high graphic design skills quickly and attractively. This research will produce interactive learning media works in interactive media design courses that are effective and achieve lecture objectives, namely increasing student creativity.